Determination of quinine in tonic water at the miniaturized and polarized liquid–liquid interface. (1st December 2021) - Rudnicki, Konrad; Sobczak, Karolina; Borgul, Paulina; Skrzypek, Sławomira; Poltorak, Lukasz
Graphical abstract: Highlights: The electrochemical investigation of QN at the µITIES is presented for the first time. The developed method has been used for the determination of QN in tonic water samples. The elaborated method is characterized by high sensitivity and repeatability. The developed procedure is highly selective when it comes to tonic water analysis. Abstract: In this work we report an electrochemical approach to quantitative and qualitative analysis of quinine (QN) at the interface between two immiscible electrolyte solutions (ITIES). This was done at the macroscopic (macroITIES) and microscopic (µITIES) systems using ion transfer voltammetry (ITV). The linear response of the peak current vs. increasing concentrations of QN at the µITIES was from 2.50 µM to 29.13 µM and the corresponding calculated limit of detection (LOD) for the current signals originating from QN transfer from the aqueous to the organic phase was equal to 0.49 µM. Additionally, the influence of pH (2–12) of the aqueous phase on the recorded QN signals was investigated. We have found that our method is fully applicable for QN direct determination in non-treated tonic water, as confirmed on three different real samples from three different manufacturers. Finally, a number of validation parameters for the developed method are provided and discussed.